Different Plant Viruses Induce Changes in Feeding Behavior of Specialist and Generalist Aphids on Common Bean That Are Likely to Enhance Virus Transmission - Wamonje, Francis O.; Donnelly, Ruairí; Tungadi, Trisna D.; Murphy, Alex M.; Pate, Adrienne E.; Woodcock, Christine; Caulfield, John; Mutuku, J. Musembi; Bruce, Toby J. A.; Gilligan, Christopher A.; Pickett, John A.; Carr, John P. (Frontiers in Plant Science, 2020)
Bean common mosaic virus (BCMV), bean common mosaic necrosis virus (BCMNV), and cucumber mosaic virus (CMV) cause serious epidemics in common bean (Phaseolus vulgaris), a vital food security crop in many low-to-medium income countries, particularly in sub-Saharan Africa. Aphids transmit these viruses ‘non-persistently’ i.e., virions attach loosely to the insects’ stylets. Viruses may manipulate aphid-host interactions to enhance transmission. We used direct observation and electrical penetration graph measurements to see if the three viruses induced similar or distinct changes in feeding behaviours of two aphid species, Aphis fabae and Myzus persicae. Both aphids vector BCMV, BCMNV and CMV but A. fabae is a legume specialist (the dominant species in bean fields) while M. persicae is a generalist that feeds on and transmits viruses to diverse plant hosts. Aphids of both species commenced probing epidermal cells (behaviour optimal for virus acquisition and inoculation) sooner on virus-infected plants than on mock-inoculated plants. Infection with CMV was especially disruptive of phloem feeding by the bean specialist aphid A. fabae. A. fabae also experienced mechanical stylet difficulty when feeding on virus-infected plants, and this was also exacerbated for M. persicae. Overall, feeding on virus-infected host plants by specialist and generalist aphids was affected in different ways but all three viruses induced similar effects on each aphid type. Specifically, non-specialist (M. persicae) aphids encountered increased stylet difficulties on plants infected with BCMV, BCMNV, or CMV, whereas specialist aphids (A. fabae) showed decreased phloem ingestion on infected plants. Probing and stylet pathway activity (which facilitate virus transmission) were not decreased by any of the viruses for either of the aphid species, except in the case of A. fabae on CMV-infected bean, where these activities were increased. Overall, these virus-induced changes in host-aphid interactions are likely to enhance non-persistent virus transmission, and data from this work will be useful in epidemiological modelling of non-persistent vectoring of viruses by aphids.